OVARYAN HİPERSTİMÜLASYON SENDROMU PATOFİZYOLOJİSİNDE TRPM2 İYON KANALI VE CHRM1 AKTİVİTELERİNİN ARAŞTIRILMASI - ŞANLI, CENGİZ (Fırat Üniveristesi, 2019)
Bu çalışmada ovaryan hiperstimülasyon sendromu (OHSS) oluşturulan ratlarda, OHSS patofizyolojisinde TRPM2 iyon kanalları ve CHRM1 aktiviteleri araştırılmıştır. Çalışmada 14 adet, 22 günlük immatür dişi Wistar Albino cinsiratın rastgele seçilen 7'sine 10 IU FSH dört gün subkutan ve beşinci gün 30 IU human koryonik gonadotropin verilerek ovaryan hiperstimülasyon oluşturuldu.. Grup 1 (n=7) 27 günlük normal, Grup 2 (n=7) 27 günlük OHSS oluşturulan grup olarak ratlar ikiye bölündü.Daha sonra tüm grupların overleri ve kan örnekleri alınıp ratlar sakrifiye edildi.Serumda VEGF, IL1, IL6, IL10, TNF? ve MDA düzeyleri,dokudaTRPM2 ve CHRM1 aktiviteleri ölçüldü. IL1 ve IL6 düzeyleri, iki grupta da benzer olup istatistiksel olarak herhangi bir farklılık izlenmedi (p>0,05). Kontrol grubu ile kıyaslandığında, OHSS grubunda IL10 (p=0,038), TNF? (p=0,007), VEGF (p=0,0017), MDA (p=0,004) düzeyleri artmış izlendi. Kontrol grubu ile kıyaslandığında, OHSS grubu over dokusunda CHRM1 (p=0.001) ve TRPM2 (p=0.001) aktiviteleri artmış izlendi. Sonuç olarak, OHSS'de çok farklı mediyatörler ve sistemler patolojiden sorumludur. TRPM2 iyon kanalları ve CHRM1 aktivitesindeki artışlar OHSS patofizyolojisine farklı bir bakış açısı oluşturmaktadır.

THE ACTIVITIES OF TRPM2 ION CHANNEL AND CHRM1 IN OVARIAN HYPERSTIMULATION SYNDROME (OHSS) In this study, TRPM2 ion channels and CHRM1 activities were investigated in the pathophysiology of ovarian hyperstimulation syndrome (OHSS). 22 days old 14 immature female Wistar albino rats divided into 2 groups randomly. 25 of them received 10 IU FSH for four days subcutenously and 30 IU human chorionic gonodotropin at fifth day for augmenting ovarian hyperstimulation. Group 1 (n = 7) normal for 27 days old, Group 2 (n = 7) rats were divided into two groups as 27 days old OHSS. Ovaries and blood samples were taken from all groups and rats were sacrificed. TRPM2 and CHRM1 activity in tissues and VEGF, IL1, IL6, IL10, TNF? , MDA levels in blood were measured. IL1 and IL6 levels were similar in two groups and no statistically significant difference was observed (p>0,05). When compared with the Control group, IL10 (p=0,038), TNF? (p=0,007), VEGF (p=0,0017) and MDA (p=0,004) levels were increased in the OHSS group. When compared with the Control group, CHRM1 (p=0,001) and TRPM2(p=0,001) levels were increased in the OHSS group's ovarian tissue. As a result, many different mediators and systems are responsible for pathology of OHSS. Increases in TRPM2 ion channels and CHRM1 activity provide a different perspective on the pathophysiology of OHSS.
The activities of trpm2 ion channel and chrm1 in ovarian hyperstimulation syndrome (OHSS)
Keywords: Kadın Hastalıkları ve Doğum